Teknologi mesin pengering pakaian berbasis limbah tempurung kelapa untuk meningkatkan ekonomi bagi UKM yang bergerak dalam bidang laundry di Kecamatan Tampan Kota Pekanbaru - Antonius Surbakti; Juandi Muhammad; Erman Taer; Ramondia Setiadi; Usman Malik (Unri Conference Series: Community Engagement, 2020)
The potential of the laundry sector, the entrepreneur community / UKM Laundry in Tampan District, which has very potential business potential. This clearly saves the huge potential of the Laundry / UKM business sector. The clothes drying system, which is carried out through the traditional drying method, has long been practised by Laundry UKM entrepreneurs. In particular, the clothes drying activity has long been a source of livelihood for the Laundry UKM community in Panam District. However, in general, the process of drying clothes through a drying method that relies solely on sunlight is not optimal. The process of drying clothes by laundry entrepreneurs in the Tampan District is still done traditionally, namely drying in the sun. This process takes a long time, it takes 2 to 4 days to dry clothes and it also depends on the presence of sunlight. The drying machine is designed to utilize heat from burning coconut shell waste which functions as a heat collector. So that the drying process can take place quickly, at any time and without depending on the sun. Control of the drying temperature is done by opening and closing the air ducts in the dryer. This dryer consists of a solar collector, biomass burning furnace, and drying room (box). The drying room functions as a place for clothes to be dried. The flow of heat from burning coconut shell waste to the drying chamber. The result of drying clothes is better than traditional drying. The drying technology based on coconut shell waste to dry clothes will be applied in the Laundry UKM community in Tampan District, Pekanbaru which is the livelihood of some UKM in Tampan District, Pekanbaru City